PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI DENGAN MODEL LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR FISIKA TOPIK CAHAYA - Fitriyah, Ida (JPPS (Jurnal Penelitian Pendidikan Sains), 2013)
This is the research of development that intends to develop learning  purchase based on inquiry by 7E learning cycle model in the light topic included syllabus, lesson plan, students book, students worksheet,  and  assesment sheet. This research is done by using  three steps, they are Development of learning instrument with Kemp model, validation of instrument and field experiment  by one group pretest-posttest design, which is done in SMPN 1 Tuban.  The result of this research is 1) Learning instrument based on inquiry by 7E learning cycle models is valid   for being done in learning: a) The result of instrumen validity refers to learning instrument in good category and it can be used in teaching learning process ; b) The difficulty level of instrument  is low a nd easy is understood by student;   c) Readablety of instrumen is high and   the materials easy is understood by students; 2) The learning instument is effective to use in learning process; a)   the value of cognitive test, performence test and affective test refer  to the improvement with high category; b) The students give a positive response to the learning process; 3) The learning instrument which has been   developed is practical to use  in learning process; a) The lesson plan that used is in a  good category; b) the hig est procentage of three student  activity are analysis the result of experiment, doing experiment / observation, and discussion/question - answer. The conclusion of the research analising   is the learning purchase which has been developed   based on inquiry by 7E learning cycle model in the light topic  have fullfiled validity, effectify and practical to use, so itis proper to use in learning process.Penelitian ini merupakan penelitian   pengembangan yang bertujuan mengembangkan   perangkat pembelajaran berbasis inkuiri dengan model learning cycle 7E topik Cahaya, meliputi Silabus, RPP, Materi ajar, LKS dan Lembar Penilaian. Penelitian ini dilaksanakan di SMPN 1 Tuban melalui tiga tahap, yaitu pengembangan perangkat dengan model Kemp, validasi perangkat, dan ujicoba lapangan dengan rancangan one group pretest-posttest. Hasil dari penelitian ini adalah 1) Perangkat Pembelajaran berbasis inkuiri dengan model Learning Cycle 7E valid untuk digunakan dalam pembelajaran; a) Hasil validasi perangkat menunjukkan perangkat pembelajaran yang dikembangkan berkategori baik dan dapat diterapkan dalam kegiatan belajar mengajar; b) Tingkat kesulitan perangkat yang dikembangkan rendah dan mudah dipahami siswa; c) Keterbacaan perangkat tinggi dan materi mudah dipahami;  2)  Perangkat pembelajaran  efektif  digunakan  dalam proses  pembelajaran;  a) Hasil  belajar kognitif  produk,  proses, psikomotor, dan  afektif menunjukkan peningkatan dengan kategori tinggi; b) Siswa memberikan respon positif terhadap perangkat pembelajaran  yang dikembangkan.  3) Perangkat  pembelajaran  yang dikembangkan  praktis  digunakan dalam pembelajaran;  a) keterlaksanaan RPP dalam kategori baik; b) Aktivitas siswa yang memiliki persentase tiga terbesar adalah menganalisis hasil percobaan, melakukan percobaan/ pengamatan, dan diskusi/tanya jawab. Penelitian ini berkesimpulan bahwa Perangkat Pembelajaran berbasis inkuiri dengan model Learning Cycle 7E topik Cahaya yang telah dikembangkan memenuhi unsur kevalidan, keefektifan dan kepraktisan, sehingga layak diimplementasikan dalam pembelajaran.